Handover Training Using Proin Ho On Self-Efficacy and Nurse Satisfaction at Anna Hospital, Bekasi City - Dewi Banjarsari; Regina VT Novita; Sudibyo Supardi (Asian Journal of Social and Humanities, 2024)
The quality of hospital services is focused on patient safety. The use of electronic technology in the form of health information improves patient safety through effective communication between health workers. A structured electronic handover process that can be used to support verbal handovers and reduce the risk of medication errors. This study aims to determine the effectiveness of the electronic Handover (Proin Ho) training program on nurses' self-efficacy and satisfaction. The research was conducted in June 2023. The research sample used a total sampling of 124 nurses with 62 respondents in each group. Quantitative Quasi Experimental research method with pre post with control group with criteria for nurses with PK level 2 and 3, following full training, willing to be respondents. The data collection tool is a questionnaire. Data analysis used t test and mutivariate backward LR linear regression. The research results showed that most of the nurses were <25-35 years old, women with D3 Nursing and PK III education. There are differences in Self-Efficacy from the 3 dimensions, most of them are good. There are differences in nurse satisfaction from the 4 dimensions, most of whom are satisfied. There was an influence on nurses' self-efficacy before and after being given the electronic handover program (Proin Ho) (p-value 0.001). There is an influence of satisfaction (p-value 0.000). Training and age are related to Self-Efficacy with p value: 0.000. Meanwhile, training ((pvalue: 0.000), age (pvalue: 0.001) and education (pvalue: 0.026) with nurse satisfaction (p<0.05).